Shotgun Approach to Increasing Enzymatic Saccharification Yields of Ammonia Fiber Expansion Pretreated Cellulosic Biomass - Chundawat, Shishir P. S.; Uppugundla, Nirmal; Gao, Dahai; Curran, Paul G.; Balan, Venkatesh; Dale, Bruce E. (Frontiers in Energy Research, 2017)
Most cellulolytic enzyme blends, either procured from a commercial vendor or isolated from a single cellulolytic microbial secretome, do not efficiently hydrolyze ammonia-pretreated (e.g., ammonia fiber expansion, AFEX) lignocellulosic agricultural crop residues like corn stover to fermentable sugars. Typically reported commercial enzyme loading (30–100 mg protein/g glucan) necessary to achieve >90% total hydrolysis yield (to monosaccharides) for AFEX-treated biomass, within a short saccharification time frame (24–48 h), is economically unviable. Unlike acid-based pretreatments, AFEX retains most of the hemicelluloses in the biomass and therefore requires a more complex suite of enzymes for efficient hydrolysis of cellulose and hemicellulose at industrially relevant high solids loadings. One strategy to reduce enzyme dosage while improving cocktail effectiveness for AFEX-treated biomass has been to use individually purified enzymes to determine optimal enzyme combinations to maximize hydrolysis yields. However, this approach is limited by the selection of heterologous enzymes available or the labor required for isolating low-abundance enzymes directly from the microbial secretomes. Here, we show that directly blending crude cellulolytic and hemicellulolytic enzymes-rich microbial secretomes can maximize specific activity on AFEX-treated biomass without having to isolate individual enzymes. Fourteen commercially available cellulolytic and hemicellulolytic enzymes were procured from leading enzyme companies (Novozymes®, Genencor®, and Biocatalysts®) and were mixed together to generate several hundred unique cocktail combinations. The mixtures were assayed for activity on AFEX-treated corn stover (AFEX-CS) using a previously established high-throughput methodology. The optimal enzyme blend combinations identified from these screening assays were enriched in various low-abundance hemicellulases and accessory enzymes typically absent in most commercial cellulases cocktails. Our simple approach of blending crude commercially available enzyme cocktails allowed a drastic fourfold reduction in total enzyme requirements (from 30 to 7.5 mg enzyme/g glucan loading) to achieve near-theoretical cellulose and hemicellulose saccharification yields for AFEX-CS.